GENETIC DIVERSITY FOR MORPHOLOGICAL AND QUALITY TRAITS IN RICE (ORYZA SATIVA L.) - BUPESH KUMAR; B. B GUPTA; BIKRAM SINGH (The Bioscan, 2014)
Nature and magnitude of genetic diversity among 23 genotypes of rice was assessed in the present study by using Mahalanobis D2 statistics. Significant variation for all the traits revealed presence of notable genetic variability among genotypes. Estimates of components of variance indicated that genotypic variance contributed maximum to phenotypic variance which suggested that available genetic variability can be exploited through selection and hybridization. Based on D2 analysis, 23 genotypes of rice were grouped into five clusters. Among the five clusters cluster III consists of 7 genotypes (IARI 1460, PB-1, Basmati 564, Pusa 1121, SJR-129, Basmati 1509 and Pusa Sugandh) forming the largest cluster followed by cluster I and IV with 5 genotypes each ( K-343, K-448, K-39, SJR51, Gizza-14 and Saanwal Basmati, RR 600, Ranbir Basmati, Basmati 370, CSR 30) cluster II with 4 genotypes (PC 19, Ratna, IET 1410, SJR 5) and cluster V with 2 genotypes (Jaya, RR 8585). Inter cluster distances were found to be higher than intra cluster distances which depicted wide genetic diversity among the rice genotypes. The contribution of various characters towards the expression of total genetic diversity indicated that 1000 grain weight contributed maximum (54.55%) followed by plant height (13.44%) and kernel breadth (11.86%). Clustering of the cultivars did not show any pattern of association between the morphological characters and the origin of the cultivars. The variability present in the material can be exploited through selection and hybridization for evolving superior rice cultivars.